Identification of Body Lengths, Height at Withers, and Rump Heights of Etawah Crossbreeds at Smallholder Farms in Kampung Bugis, Serangan Village, Bali - I. F., Ramadhani; Doloksaribu, L.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
The purpose of this study was to identify body dimensions that influenced the growth of goats reared in Bugis Village, Serangan Village, Bali. Data was obtained through direct observations, formal goat farmer interviews and key informant interviews that were conducted from July to September 2018. Two out of the remaining three farmers who keep rearing goats in Serangan Village were involved in this study. Each farmer housed his goats with a colony housing system and fed forages ± 10% of body weight/goat/day but only one farmer provided additional probiotic mixtures with drinking water given ad libitum to the goats. The variables observed were body lengths, height at withers, and rump heights. Result of this study showed that the average of total body lengths of control goat 86.7 ± 2.4 cm was significantly longer than 79.6 ± 2.4 cm of the treatment goats. The average of total height at withers of control goats 63.9 ± 0.8 cm was significantly higher than 58.4 ± 2.2 cm of the treatment goats. The average of total rumph height of the control goats 63.4 ± 0.6 cm tended to be higher than 59.5 ± 1.5 cm of the treatment goats. Result showed that the average of body dimension of the control goats was larger than of the treatment goats, due to the control goats only had 2 I 0 (25%) while the treatment goats had 11 I 0 (young goats aged less than 1 year old) (61%). This research proved that administering a mixture of probiotics with drinking water given ad libitum had an important role in supporting the growth of body dimension especially the older goats (I 1 , I 3 , I 4 , and toothless). Keywords: Etawah crossbreeds, body lengths, height at withers, and rump heights